Analysis of Gunung Api Purba Nglanggeran Tourist Destination on Tourist Satisfaction - Nurhidayati, Hindun; Mashita, Azra; Sahra, Zagita; Reihani, Pradisha; Gunadi, I Made Adhi (International Journal of Travel, Hospitality and Events, 2025)
Purpose: This study aims to analyze what factors influence tourist satisfaction in tourist destination Gunung Api Purba Nglanggeran. Research methods: This is a quantitative research with simple linear regression analysis, and the use of SPSS 23 in processing data. The data collected using google form with 70 respondents from tourists who visited Gunung Api Purba Nglanggeran. Results and discussion: The findings of this study indicate that tourist destinations influence the tourist satisfaction positively. Meanwhile, this study finds that amenity and accessibility in tourist destinations need to be improved. Implication: This research was conducted to provide developments in the Gunung Api Purba Nglanggeran. This research suggests that this destination should further improve existing amenities and accessibility to increase visitor satisfaction.